Textbook typologies: Challenging the myth of the perfect obstetric pelvis. Issue 4 (24th February 2022) - VanSickle, Caroline; Liese, Kylea L.; Rutherford, Julienne N.
Abstract: Medical education's treatment of obstetric‐related anatomy exemplifies historical sex bias in medical curricula. Foundational obstetric and midwifery textbooks teach that clinical pelvimetry and the Caldwell–Moloy classification system are used to assess the pelvic capacity of a pregnant patient. We describe the history of these techniques—ostensibly developed to manage arrested labors—and offer the following criticisms. The sample on which these techniques were developed betrays the bias of the authors and does not represent the sample needed to address their interest in obstetric outcomes. Caldwell and Moloy wrote as though the size and shape of the bony pelvis are the primary causes of "difficult birth"; today we know differently, yet books still present their work as relevant. The human obstetric pelvis varies in complex ways that are healthy and normal such that neither individual clinical pelvimetric dimensions nor the artificial typologies developed from these measurements can be clearly correlated with obstetric outcomes. We critique the continued inclusion of clinical pelvimetry and the Caldwell–Moloy classification system in biomedical curricula for the racism that was inherent in the development of these techniques and that has clinical consequences today. We call for textbooks, curricula, and clinical practices to abandon these outdated, racist techniques. In their place, we call for a truly evidence‐based practice of obstetrics and midwifery, one based on an understanding of the complexity and variability of the physiology of pregnancy and birth. Instead of using false typologies that lack evidence, this change would empower both pregnant people and practitioners.